(untitled) (European Journal of Mental Health, 2022)
Introduction: A person experiencing mental health issues may be physically confined at the suggestion of an informal leader who sees that individual’s violent behavior as a threat to the community. Aims: The aim of the study is to explore the perceptions of the tu’a golo, a man who serves as informal village leader, regarding his role in confining a person with mental health issues in Manggarai, on the island of Flores, in Indonesia. Methods: The study uses an ethno-semantic approach. Data collection and analysis were carried out using Spradley’s Developmental Research Sequence; the researchers interviewed one tu’a golo from each of fifteen villages in Manggarai. They then analyzed the data via using domain, taxonomy, componential, and cultural themes. Results: The researchers found that the tu’a golo has three important roles in confining a person with mental health issues: (1) before physical restraint and confinement, as an adviser to the family and to the person exhibiting mental health issues; (2) before physical restraint and confinement, as a mediator between the family of the individual with mental health issues and the community; (3) during physical restraint and confinement, as a protector of the person with mental health issues, the family, and the community. Conclusions: In areas with limited mental health services, informal leaders take on important roles in the physical restraint and confinement of the mentally ill. Therefore, healthcare professionals must include informal leaders in programs to improve mental health services and reduce the use of physical restraint and confinement.